The future of freight transport technology for bulk materials through scenario building - Garcia, Jezekiel G. (University of the Philippines Diliman, 2022)
No one predicted that the COVID-19 pandemic would hit the world this 2020. The bulk transport industry has been affected by a series of lockdowns, strict health and safety protocols, heavy quarantine procedures, skeletal workforces, layoffs, and new compliances. International air travel disrupted backlogs, staff shortages, and travel restrictions in the US, EU, and CN. Amid the hype of increasing e-commerce demand, numerous supply chain disruptions have happened, including port congestion causing delays on import and export operations, Canal Suez blockages March 2021, spikes in jet fuel costs and high freight cost charges, while the whole world has started to roll out vaccines in different countries. Alongside, the whole industry has already experienced many uncertainties, opportunities, and threats before, including transport security risks, climate change, inadequate infrastructure, and lack of technological advancement. This crisis made the bulk transport industry rethink alternative solutions to transform into safe, secure, and sustainable operations.